קאופמן, שלום א׳, אכדית וארמית בבלית הדדית הבהרה מאדווֹגות הדשות כ - Kaufman, Stephen A.
Akkadian and Babylonian Aramaic. New Examples of Mutual Elucidation; amāru ‘brick pile’; esittu ‘mortar’; pattû ‘bucket’; pattu ‘canal’.